2007
DOI: 10.1002/eji.200636372
|View full text |Cite
|
Sign up to set email alerts
|

No essential role for tripeptidyl peptidase II for the processing of LCMV‐derived T cell epitopes

Abstract: The proteasome is critically involved in the production of MHC class I-restricted T cell epitopes. Approximately 20% of all peptides generated by the proteasome are too large for direct presentation by MHC class I molecules. Reits et al. (Immunity 2004. 20: 495-506) suggested that a major portion of proteasomal products are larger than 15 amino acids and require further degradation by the tripeptidyl peptidase II (TPPII) before becoming ligands of MHC class I molecules. Using the well-characterized lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
6
26
1
Order By: Relevance
“…A "model Ag," a "model peptide precursor" (i.e., OVA), and a well-known viral epitope have been applied to study the enzymatic activity of cytosolic peptidases (11, 12, 17, 36 -38). However, the function of certain peptidases in the presentation of MHC class I Ags in in vitro and in vivo systems, as well as the model Ags used in each case, have been controversial (8,10,12,36,39,40). Rock and colleagues showed that the trimming of antigenic peptides in LAP-, BH-, or PSA-deficient mice was not reduced and that there was no significant difference in the presentation of OVA8 from N-terminally extended precursors or full-length OVA (11,12,36).…”
Section: Discussionmentioning
confidence: 99%
“…A "model Ag," a "model peptide precursor" (i.e., OVA), and a well-known viral epitope have been applied to study the enzymatic activity of cytosolic peptidases (11, 12, 17, 36 -38). However, the function of certain peptidases in the presentation of MHC class I Ags in in vitro and in vivo systems, as well as the model Ags used in each case, have been controversial (8,10,12,36,39,40). Rock and colleagues showed that the trimming of antigenic peptides in LAP-, BH-, or PSA-deficient mice was not reduced and that there was no significant difference in the presentation of OVA8 from N-terminally extended precursors or full-length OVA (11,12,36).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations regarding the proteasome-dependent epitope SIINFEKL derived from OVA also did not prove a dependency on TPPII, because siRNA-mediated inhibition did not reduce epitope presentation (44) and TPP Ϫ/Ϫ cells of a knockout mouse were even better in presenting this epitope (45). Other proteasome-dependent epitopes have also been analyzed regarding TPPII involvement in epitope processing, but no effect could be demonstrated both in in vivo and ex vivo experiments (26,45,46). A different conclusion can be drawn from the so-called unusual epitopes that are presented better with a proteasomal blockade and may be generated by a different protease.…”
Section: Discussionmentioning
confidence: 99%
“…Transfections B8 cells overexpressing LMP7 and H-2D b (B8-LMP7/D b ) were transfected with an expression plasmid encoding b1WT-myc/His or b1T1A-myc/His, as previously described, using FuGene 6 (Roche, Basel, Switzerland) (28). Clonal and blasticidin (Invitrogen Life Technologies; 5 mg/ml)-resistant cells were tested for b1WT or b1T1A expression by Western blot.…”
Section: Cloningmentioning
confidence: 99%